The real Mrs. Tobias : a novel - Koslow, Sally (Harper, an imprint of HarperCollins Publishers, 2022)
"A warm and witty multigenerational story about the deeply complicated relationships between mothers- and daughters-in-law, told through three women who marry into the same family. It's 2018 in New York City, and three women all known as Mrs. Tobias--Veronika, the matriarch, her daughter-in-law Mel, and Mel's daughter-in-law Birdie--are trying to navigate personal difficulties, some of which are with one another. Veronika and Mel, despite having little in common, are both psychotherapists who are more skilled at helping other people than solving their own problems. Birdie, still dealing with the culture shock of moving to New York City and marrying into the Tobias clan, is pushed to her limit when her husband, Micah, gets into trouble. No amount of badgering from his steely grandmother, smart-mouthed mother, or disillusioned wife can convince Micah to own up to what he's done. Overwhelmed, Birdie bolts--taking along with their young daughter--to her Midwestern hometown, hoping that space, warmth and wisdom from her own feisty grandmother will help her find a path forward. And though Birdie begins to find comfort in a local bookstore and in the arms of her old boyfriend, back in New York her absence stirs up long simmering troubles and forces the Tobiases to reconsider their relationships to one another, and ultimately, what it means to be a family."--